PENGARUH PEMBERIAN TINDAKAN BREASTFEEDING TERHADAP INTENSITAS NYERI IMUNISASI PADA BAYI DI DESA LEDONG KECAMATAN AEK LEDONG KABUPATEN ASAHAN - barus, dewi tiansa; Yanti, Mutiara Dwi (Jurnal Penelitian Keperawatan Medik, 2021)
Immunization is an invasive action that is painful for toddlers. Moreover, most injections are given early in the life of children. Even children can receive up to 20 injections until they reach the age of 2 years. Pain that is felt during immunization makes toddlers experience uncomfortable experiences that affect the development of the central nervous system. Breastfeeding is a non-pharmacological pain management technique that can reduce the intensity of pain in infants when immunization is complete. This type of research is included in quantitative research. This research uses quasy experimental research method. The type of design used is nonequivalent control group design namely there are 2 groups of control and experiment. In this study the sampling technique used was purposive sampling. The number of samples of this study were 12 respondents. Data collection using observation sheets and data analysis used is the Independent t test. The research results obtained from the Independent Sample Test obtained the average value of the control group was 7.17 with SD 2.31. While the average value of the intervention group was 3.83 with an SD of 2.40. So there is an average difference between the two groups. Sig. Value (2-tailed) of 0.03 <0.05, it was concluded that Ho was rejected Hi was accepted. Thus it can be concluded that there is an Effect of Provision of Breastfeeding Actions on the Intensity of Immunization Pain in Infants in Ledong Timur Village, Aek Ledong District, Asahan Regency.